Experiences from Public-Private partnerships across Europe - Timmermans, Toine (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
This presentation is part of the Wageningen University & Research food loss and waste project, the presentation Experiences from Public-Private partnerships across Europe was presented by Toine Timmermans in June of 2017.